ARTISTIC IMAGINATION AND FANTASY OF STUDENTS IN VISUAL ART LESSONS. THEIR ROLE IN ARTISTIC CREATION - Imomatova Umida Mirpulatovna (Web of Journals Publishing, 2024)
The article explores the significance of artistic imagination and fantasy in the development of students' creativity during visual art lessons. It examines how these faculties play a central role in shaping students' artistic expression, helping them not only to acquire technical skills but also to develop their unique visual language. Artistic imagination, defined as the ability to envision and create new ideas or forms from one's inner world, allows students to transcend the limits of reality and engage in creative problem-solving. Fantasy, on the other hand, provides the emotional and psychological depth that enables students to express abstract concepts and complex emotions through visual media.
Keywords: mastering, student, imagination, fantasy, art, artistic, pedagogical.